SLANG WORDS FOUND IN 1999 SONG ALBUM BY RICH BRIAN’S - Dewa Ayu Made Ratna Dwiyanti Yanti (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
There are many English songs use slang words, especially in rap songs. Because, it can make interesting lyrics in the songs. Such English slang words can be classified into different types and the formations are interesting to study. Therefore, the study is about the slang words found in 1999 song album by Rich Brian’s. It aimed to identify the types of the slang words and the process of creating the words. The data obtained through listening to the songs, reading and understanding the lyrics, marking the words in the lyrics, before identifying the types, and analyzing the formations. In collecting the data, this study used the observation method. For such goals it used the theory by Kipfer and Chapman and Mattielo and analyzed by using a descriptive qualitative method. In analysis, for the types of slang, the study found only secondary slang. And for the process of creating the words, there were only 3 kinds of formation that were found, namely clipping, blending, and variation.